Efficient Flotation Separation of Antimonate Minerals from Quartz Using Sodium Dodecyl Sulfonate as Collector - Feng Jiang; Pengyuan Wang; Jiaxing Qi; Wei Sun; Yulin Zhou; Weishang Zhao; Shuai He; Yuanjia Luo; Honghu Tang (Metals)
The efficient separation of antimonate minerals from quartz remains a significant challenge in mineral processing due to their similar surface properties and strong hydrophilicity. This study explored the application of sodium dodecyl sulfonate (SDS) as a selective collector for antimonate–quartz flotation separation. Micro-flotation tests demonstrated that SDS achieved optimal recovery of antimonate minerals (90.25%) at pH 8 with a dosage of 70 mg/L, while quartz recovery remained below 10%. Contact angle measurements revealed a significant increase in the hydrophobicity of antimonate minerals after SDS treatment, whereas quartz remained highly hydrophilic. FTIR and XPS analyses confirmed the selective chemisorption of SDS on antimonate mineral surfaces through Sb-O-S bond formation, while negligible adsorption occurred on quartz. Adsorption isotherms further showed the higher SDS uptake on antimonate minerals compared to quartz. These findings collectively demonstrate the effectiveness of SDS as a selective collector for the flotation of antimonate minerals, providing a promising approach to enhancing the recovery of fine antimonate particles.